2016
DOI: 10.17159/1947-9417/2016/732
|View full text |Cite
|
Sign up to set email alerts
|

'Youth amplified': using critical pedagogy to stimulate learning through dialogue at a youth radio show

Abstract: In this paper I describe and analyse how critical pedagogy, an approach to teaching and learning that encourages students to reflect on their socio-political contexts, may stimulate critical consciousness and dialogue at a youth radio show. The participants, who attended four diverse Cape Town high schools and predominantly lived in poor townships, named the show Youth Amplified. Youth Amplified dialogues were catalysed by a range of materials, including documentary films, newspapers and academic articles, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The reverse side of the empowerment discourse in critical pedagogy that further highlights the complexity of learning to teach, is the teacher's own disempowerment. Several South African studies have demonstrated the affordances of critical pedagogy in the empowerment of the youth (Cooper, 2016;Mayaba et al, 2018). But what is often missed is the pervasive sense of disempowerment teachers may experience as they encounter a school curriculum that leaves little opportunity for independent intellectual work with learners.…”
Section: Preparation Vs Opportunity: Critical Pedagogy and Learning T...mentioning
confidence: 99%
“…The reverse side of the empowerment discourse in critical pedagogy that further highlights the complexity of learning to teach, is the teacher's own disempowerment. Several South African studies have demonstrated the affordances of critical pedagogy in the empowerment of the youth (Cooper, 2016;Mayaba et al, 2018). But what is often missed is the pervasive sense of disempowerment teachers may experience as they encounter a school curriculum that leaves little opportunity for independent intellectual work with learners.…”
Section: Preparation Vs Opportunity: Critical Pedagogy and Learning T...mentioning
confidence: 99%
“…Research has focused on the use of dialogic groups as a successful method of teaching students social justice and equity particularly within the context of critical pedagogy and intergroup dialog (Aliakbari and Faraji, 2011; Lopez and Zúñiga, 2010). One study highlighted how promoting dialog on social justice through critical pedagogy in a diverse group of South African youths led to the development of critical consciousness and social reflexivity (Cooper, 2016). Critical pedagogy through dialog allows for discussion between teachers and students where all members are equally respected.…”
Section: Dialogic Small Group Learningmentioning
confidence: 99%
“…I was attracted to the youth radio show, in which seven RGHS students participated, because it comprised a form of what Ladson-Billings (1995) called culturally relevant pedagogy that connects with students' sociopolitical challenges. Youth Amplified utilised a form of critical pedagogy, exposing participants to materials that dealt with the sociopolitical contexts in which they lived (see Cooper, 2016). Participants engaged in debates and discussions, live on air, after watching documentary films or reading written texts prior to the show.…”
Section: Multisite Linguistic Ethnographymentioning
confidence: 99%